N‐acetylaspartate release by glutaminolytic ovarian cancer cells sustains protumoral macrophages. (14th July 2021) - Menga, Alessio; Favia, Maria; Spera, Iolanda; Vegliante, Maria C; Gissi, Rosanna; De Grassi, Anna; Laera, Luna; Campanella, Annalisa; Gerbino, Andrea; Carrà, Giovanna; Canton, Marcella; Loizzi, Vera; et al.
Abstract: Glutaminolysis is known to correlate with ovarian cancer aggressiveness and invasion. However, how this affects the tumor microenvironment is elusive. Here, we show that ovarian cancer cells become addicted to extracellular glutamine when silenced for glutamine synthetase (GS), similar to naturally occurring GS‐low, glutaminolysis‐high ovarian cancer cells. Glutamine addiction elicits a crosstalk mechanism whereby cancer cells release N ‐acetylaspartate (NAA) which, through the inhibition of the NMDA receptor, and synergistically with IL‐10, enforces GS expression in macrophages. In turn, GS‐high macrophages acquire M2‐like, tumorigenic features. Supporting this in␣vitro model, in silico data and the analysis of ascitic fluid isolated from ovarian cancer patients prove that an M2‐like macrophage phenotype, IL‐10 release, and NAA levels positively correlate with disease stage. Our study uncovers the unprecedented role of glutamine metabolism in modulating macrophage polarization in highly invasive ovarian cancer and highlights the anti‐inflammatory, protumoral function of NAA. Synopsis: This study reveals a crosstalk between ovarian cancer cells and tumor associated macrophages. Glutamine addicted cancer cells release the signaling metabolite N ‐acetylaspartate (NAA), which in turn polarizes macrophages towards a GS‐high, M2‐like state. Glutaminolysis upon GS silencing in ovarian cancer cells leads to the release of NAA, which acts synergically with IL‐10 to polarize macrophages toward a GS‐high, M2‐ like phenotype. NAA acts as a competitor of the NMDA receptor (NMDAR) ligand. Concomitant treatment with NMDA abrogates the effect of NAA on LPS/IFNγ macrophages. The GS levels in macrophages from the ascitic fluid of ovarian cancer patients correlate with the cancer stage, ascitic IL‐10 and NAA levels. Abstract : This study reveals a crosstalk between ovarian cancer cells and tumor associated macrophages. Glutamine addicted cancer cells release the signaling metabolite N ‐acetylaspartate (NAA), which in turn polarizes macrophages towards a GS‐high, M2‐like state.